2017
DOI: 10.1016/j.pmrj.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Circuit‐Based Exercises on Gait Speed, Balance, and Functional Mobility in People Affected by Stroke: A Meta‐Analysis

Abstract: I.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 34 publications
0
9
0
4
Order By: Relevance
“…Physiotherapists have initiated clinical trials of stroke recovery processes and rehabilitation therapy sessions. One ongoing study includes a strategy to manage disability by improving mobility using treadmill exercise, electromechanical device therapy and circuit class therapy [ 164 , 165 ]. Stroke Recovery and Rehabilitation Roundtables bring physiotherapists and other experts together to recommend research directions and produce guidance for the post-stroke healthcare system.…”
Section: Trends In Stroke Researchmentioning
confidence: 99%
“…Physiotherapists have initiated clinical trials of stroke recovery processes and rehabilitation therapy sessions. One ongoing study includes a strategy to manage disability by improving mobility using treadmill exercise, electromechanical device therapy and circuit class therapy [ 164 , 165 ]. Stroke Recovery and Rehabilitation Roundtables bring physiotherapists and other experts together to recommend research directions and produce guidance for the post-stroke healthcare system.…”
Section: Trends In Stroke Researchmentioning
confidence: 99%
“…One small meta-analysis (5 RCTs; N=159 participants) compared dance interventions (Tango or Irish) with other physical activity interventions (3 RCTs) Stroke.-In the 2018 PAGAC Scientific Report, moderate evidence indicated that mobilityoriented physical activity improved walking function for individuals after a stroke and that among stroke survivors, treadmill walking (especially with cadence cuing) improved walking speed by approximately 0.23m/sec (8). Seven systematic reviews relating physical activity to improved physical function in people having had a stroke were identified from the updated search (53)(54)(55)(56)(57)(58)(59). Of these reviews, 6 included a meta-analysis (53)(54)(55)(56)(57)(58).…”
Section: Physical Activity and Physical Function In Older People Withmentioning
confidence: 99%
“…Seven systematic reviews relating physical activity to improved physical function in people having had a stroke were identified from the updated search (53)(54)(55)(56)(57)(58)(59). Of these reviews, 6 included a meta-analysis (53)(54)(55)(56)(57)(58). The interventions examined included aerobic exercise (54), circuit-based training (53), dual-task balance and mobility training (56), progressive task-oriented exercise (58), and treadmill training (57,59).…”
Section: Physical Activity and Physical Function In Older People Withmentioning
confidence: 99%
“…Hemiplegic gait manifests a lack of symmetry between the paretic side and the non-paretic side [32] .…”
Section: Gait Symmetrymentioning
confidence: 99%